Self-Sacrifice Is Not the Only Way to Practice Filial Piety for Chinese Adolescents in Conflict With Their Parents - Wu, Chih-Wen; Yeh, Kuang-Hui (Frontiers in Psychology, 2021)
We applied the theoretical perspective of the dual filial piety model to consider the diversity of parent-child conflict resolution strategies in order to determine whether Chinese adolescents use strategies other than self-sacrifice to practice filial piety when in conflict with their parents. Study 1 utilized a cross-sectional design with 247 valid responses. The structural equation modeling analysis indicated that Taiwanese adolescents’ authoritarian filial piety (AFP) beliefs are positively related to use of a self-sacrifice strategy, and reciprocal filial piety (RFP) beliefs are positively related to use of compatibility and compromise strategies. Adolescents’ AFP and RFP beliefs are negatively related to use of utility and escape strategies. Study 2 applied a temporal separation procedure with a 1-year lag to remedy common method variance bias. Analysis of 1,063 valid responses replicated the findings of Study 1 and indicated that adolescents’ function-oriented appraisal of conflict can play a mediating role between RFP and the use of the compatibility and compromise strategies. These findings broaden the understanding of filial piety in modern Chinese societies and have implications for adolescents’ well-being and family life.